1988
DOI: 10.1148/radiology.169.2.2845470
|View full text |Cite
|
Sign up to set email alerts
|

Occult malignant breast lesions in 114 patients: relationship to age and the presence of microcalcifications.

Abstract: This study evaluates the mammographic findings in 352 patients, aged 30-85 years, who underwent spot localization and biopsy for evaluation of nonpalpable breast abnormalities. Malignancy was found at biopsy in 114 cases. The mammographic appearance (specifically, whether grouped microcalcifications, mass, or both were present) was correlated with patient age and histologic findings (specifically, whether the pathologic changes were infiltrating or noninfiltrating in nature). The prevalence of malignant condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 0 publications
1
18
0
1
Order By: Relevance
“…2,3,14,15 In addition to young age, the presence of mammographic calcification has also been associated with higher rates of local recurrence. 16 Because we and others 8,9,11 found that calcifications detected by screening mammography in young patients are more frequently a manifestation of DCIS, the value of mammography in young patients may be increasing. In addition, local recurrence is more frequent with cancers with extensive intraductal carcinoma manifesting as calcifications.…”
Section: Discussionmentioning
confidence: 97%
“…2,3,14,15 In addition to young age, the presence of mammographic calcification has also been associated with higher rates of local recurrence. 16 Because we and others 8,9,11 found that calcifications detected by screening mammography in young patients are more frequently a manifestation of DCIS, the value of mammography in young patients may be increasing. In addition, local recurrence is more frequent with cancers with extensive intraductal carcinoma manifesting as calcifications.…”
Section: Discussionmentioning
confidence: 97%
“…Besides, there were statistically differences of calcification performance rate between different age groups. Proved by pathology, microcalcifications revealed by mammography in young patients were more frequently a manifestation of DCIS (Hermann et al, 1988;Papatestas et al, 1990;Evans et al, 1997). Even invasive malignancies presenting as calcifications also associated with extensive intraductal carcinoma (Healey et al, 1989;Schmidt-Ullrich et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of only two comparable large, prospective studies-one limited to screening examinations followed by biopsy recommendation and one limited to screening examinations followed by open biopsy in a Singaporean population (5,28). Compared with prior studies limited to biopsied breasts, we enabled more accurate determination of true-versus false-positive results by including outcomes on all findings through Surveillance Epidemiology and End Results linkage (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Most prior studies are retrospective, small, at a single site, and have limited generalizability.…”
Section: Strengthsmentioning
confidence: 99%
“…Investigators in most prior studies have not comprehensively assessed cancer outcomes, for they assessed cancer status only in patients who underwent biopsy, which led to socalled verification bias, and, thus, they less accurately characterized the predictive value of mammographic findings compared with tumor registry linkage (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In addition, most prior studies were single center based, and, thus, they may have yielded nongeneralizable results.…”
mentioning
confidence: 99%